2012
DOI: 10.1186/1471-2229-12-71
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of unstable expression of high gamma-tocopherol content in sunflower seeds

Abstract: BackgroundTocopherols are natural antioxidants with both in vivo (vitamin E) and in vitro activity. Sunflower seeds contain predominantly alpha-tocopherol (>90% of total tocopherols), with maximum vitamin E effect but lower in vitro antioxidant action than other tocopherol forms such as gamma-tocopherol. Sunflower germplasm with stable high levels of gamma-tocopherol (>85%) has been developed. The trait is controlled by recessive alleles at a single locus Tph2 underlying a gamma-tocopherol methyltransferase (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
15
2
Order By: Relevance
“…Loss of function of γ -TMT has resulted in nearly complete replacement of α -tocopherol by γ -tocopherol in sunflower [ 26 ] and safflower [ 27 ]. The opposite situation, that is, increased α -tocopherol and reduced γ -tocopherol relative concentrations, has been reported to occur due to higher activity of the γ -TMT promoter in soybean [ 28 ], to the presence of additional active copies of the γ -TMT gene in sunflower [ 29 ], and also to induction by overexpression of the γ -TMT gene in several species such as Arabidopsis , soybean, and Brassica juncea [ 13 , 30 32 ]. The Ethiopian mustard line BCT-6 showed a reduction of total γ -tocopherol content in addition to a change in the relative proportion of α - and γ -tocopherol, which has not been reported in any of the abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of γ -TMT has resulted in nearly complete replacement of α -tocopherol by γ -tocopherol in sunflower [ 26 ] and safflower [ 27 ]. The opposite situation, that is, increased α -tocopherol and reduced γ -tocopherol relative concentrations, has been reported to occur due to higher activity of the γ -TMT promoter in soybean [ 28 ], to the presence of additional active copies of the γ -TMT gene in sunflower [ 29 ], and also to induction by overexpression of the γ -TMT gene in several species such as Arabidopsis , soybean, and Brassica juncea [ 13 , 30 32 ]. The Ethiopian mustard line BCT-6 showed a reduction of total γ -tocopherol content in addition to a change in the relative proportion of α - and γ -tocopherol, which has not been reported in any of the abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…García‐Moreno et al. () reported that the presence of several copies of γ‐TMT contributed to α‐tocopherol accumulation in a sunflower mutant in which the main γ‐TMT locus was altered. Further studies are required to elucidate the molecular mechanisms leading to either reduced or increased levels of the α/γ‐tocopherol ratio in the Ethiopian mustard lines developed in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…High γ‐tocopherol content is produced by recessive alleles at Tph2 whereas high δ‐tocopherol content is the result of epistatic interaction of recessive alleles at the three loci (Hass et al, 2006). A recent molecular analysis revealed that the two lines with high γ‐tocopherol content used in the present research, T2100 and IAST‐1, carry different alleles at the same locus Tph2 (García‐Moreno et al, 2012). In both cases, high γ‐tocopherol content showed high environmental stability, with overall coefficients of variation over 14 environments below 1%.…”
Section: Discussionmentioning
confidence: 63%